Establishment of a Blocking ELISA Detection Method for Against African Swine Fever Virus p30 Antibody - Yu, Xuexiang; Zhu, Xianjing; Chen, Xiaoyu; Li, Dongfan; Xu, Qian; Yao, Lun; Sun, Qi; Ghonaim, Ahmed H.; Ku, Xugang; Fan, Shengxian; Yang, Hanchun; He, Qigai (Frontiers in Veterinary Science, 2021)
African swine fever (ASF) is a highly lethal hemorrhagic viral disease of domestic pigs caused by African swine fever virus (ASFV). A sensitive and reliable serological diagnostic assay is required, so as laboratories can effectively and quickly detect ASFV infection. The p30 protein is abundantly expressed early in cells, and has excellent antigenicity. So, this study aimed to produce and characterize p30 monoclonal antibodies with an ultimate goal of developing a monoclonal antibody-based enzyme-linked immunosorbent assay (ELISA) for ASFV antibodies detection. Three monoclonal antibodies against p30 protein that was expressed in E.coli were generated and their characterizations were investigated. Furthermore, a blocking ELISA based on a monoclonal antibody was developed. To evaluate the performance of the assay, 186 sera samples (88 negative and 98 positive samples) were analyzed and a receiver-operating characteristic (ROC) analysis was applied to determine the cut-off value. Based on the ROC analysis, the area under the curve (AUC) was 0.997 (95% confidence interval: 99.2% to100%). Besides, a diagnostic sensitivity of 97.96% (95% confidence interval: 92.82% to 99.75%) and a specificity of 98.96% (95% confidence interval: 93.83% to 99.97%) were achieved when the cut-off value was set to 38.38%. Moreover, the coefficients of inter-and intra-batches were less than 10%, indicating the good repeatability of the method. The maximum dilution of positive standard serum detected by this ELISA method was 1:512. The blocking ELISA was able to detect seroconversion in two out of five pigs at 10 Dpi and the p30 response increasing trend through the time course of the study (0-20Dpi). In conclusion, the p30 mAb-based blocking ELISA developed in this study demonstrated a high repeatability with maximized diagnostic sensitivity and specificity. The assay could be a useful tool for field surveillance and epidemiological studies in swine herd.